"Hapless Victims" or "Making Trouble": Audience Responses to Stereotypical Representations of Asylum Seekers in Australian News Discourse. (2nd January 2023) - Haw, Ashleigh L.
ABSTRACT: Despite its long history of resettling refugees, Australia's acceptance of asylum seekers continues to attract considerable debate and division. This is exacerbated by news coverage that constructs people seeking asylum along a "threat" versus "victim" binary. As most Australians lack direct experience with people from asylum seeking backgrounds, media discourse plays a pivotal role in societal understandings of the issue. This paper discusses research combining Critical Discourse Analysis with a cultural studies Audience Reception epistemology to examine how 24 Western Australians respond to news representations of asylum seekers. Participants drew upon their own perspectives when discussing Australian coverage, highlighting the importance of accounting for audiences' ideological positioning when examining their perspectives on news discourse. While some accepted dominant constructions of asylum seekers as a "threat" and argued that the "victim" narrative is emotionally manipulative, others rejected both tropes, positing that the former legitimises asylum seekers' exclusion while the latter portrays them as deficient and agentless. These findings are discussed with consideration of their implications - in both a practice and scholarly context—demonstrating the value of applying critical discourse methods in audience reception research.